A Secure Data Transmission By Integrating Cryptography And Video Steganography - P K, Shafna (IJRDO -Journal of Computer Science Engineering, 2015)
Advances in digital content transmission haveincreased in past few years. Security and privacy issues of thetransmitted data have become an important concern inmultimedia technology. In this paper proposes a videosteganography method for transmitting data securely.Steganography means covered writing it includes process ofconcealing information within other file and also conceals thefact that a secret message is being sent .Video Steganography isto hide the existence of the message from unauthorized partyusing Video as cover file and hiding data in video. In this worka very simple and real time algorithm is used for theencryption of the images which are the basic building blocks ofany video file. In the proposed research paper the video isdistributed into the photo frames using a matlab code and allthe frames are sequentially stored. Each such frame contains acombination of red, blue and green layers. If we consider apixel as an 8 bit value than each pixel has the value in therange of 0 to 255. In this work, for each frame four pixelssituated at the top left and right and the bottom left and rightcorner are modified so as to insert text in each image. Textdata is encrypted using AES algorithm. After the completion ofthe pixel value changing all the images is placed in a sequentialmanner and then all the frames are cascaded for generation ofthe original video file with encryption. This new video is almostsimilar to the original video file with no changes visible to thenaked eye.